Vrednotenje upravnih e-portalov - Leben, Anamarija (Uporabna informatika (Ljubljana), 2005)
Electronic government portals have become a major platform for the provision of electronic public services to users, citizens and organisations. The quality and friendliness of these portals depend on their design and level of sophistication. In the first part of the article, we describe some major current approaches to the evaluation of e-services and government e-portals. In the second part, we present our own methodology, which was designed with thw attempt to globally assess the characteristics of the so-colled life-event portals. The evaluation includes the level of sophistication, scope, coordination and accessibility of services, which are aggregated at theportal level. In the last part, we present empirical results of this methodology applied to twelve government e-portals worldwide.
Keywords: elektronsko poslovanje; javna uprava; portali; vrednotenje